SYSTEMATIC LITERATURE REVIEW: PENGGUNAAN MEDIA PEMBELAJARAN KOMIK PADA MATERI BIOLOGI - Brillian Nurin Nada; Erna Wijayanti (BIO-EDU: Jurnal Pendidikan Biologi, 2023)
Media in learning is very helpful in launching teaching and learning activities to achieve learning objectives. There are various types of media that can be used in learning activities, one of which is comic media. However, not all material can be delivered with these media, so an article review is needed to summarize the results of previous research related to the use of comic media using the systematic literature review method. The purpose of this study is to find out biology material that has used comic media and the influence of the development and application of comic media in biology learning, so that it can be used as a reference in determining learning media, especially comics, which are in accordance with learning materials. This study examined 23 journal articles with a span of the last 12 years related to the development or use of comic media both at the junior high / high school level on biological material. The result of the article review is that there are 16 biological materials that have used comic media. While the development of comic media shows the average results of validation with valid categories, usage tests with very good categories and the feasibility of comic media shows decent categories. The application of comic media shows the results of increasing learning outcomes, learning motivation and learning implementation.